Thickness dependence of the MoO(3) blocking layers on ZnO nanorod-inverted organic photovoltaic devices - Wang, Mingjun (American Institute of Physics, 2011)
Organic solar cells based on vertically aligned zinc oxide nanorod arrays (ZNR) in an inverted structure of indium tin oxide (ITO)∕ZNR∕poly(3-hexylthiophene): (6,6)-phenyl C61 butyric acid methyl ester(P3HT:PCBM)∕MoO(3)∕aluminum(Al) were studied. We found that the optimum MoO(3) layer thickness condition of 20 nm, the MoO(3) can effectively decrease the probability of bimolecular recombination either at the Al interface or within the active layer itself. For this optimum condition we get a power conversion efficiency of 2.15%, a short-circuit current density of 9.02 mA∕cm(2), an open-circuit voltage of 0.55V, and a fill factor of 0.44 under 100 mW∕cm(2) irradiation. Our investigations also show that the highly crystallized ZNR can create short and continuous pathways for electron transport and increase the contact area between the ZNR and the organic materials.